MICROBIOLOGICAL PROFILE AND ANTIBIOGRAM OF LOWER RESPIRATORY TRACT INFECTIONS AT LAHORE GENERAL HOSPITAL, LAHORE - Malik, Muna; Malik, Muhammad Irfan; Akhtar, Fahd Kamal (Journal of Postgraduate Medical Institute, 2019)
Objectives: To identify the microbial pathogens that are responsible for lower respiratory tract infections in a tertiary care hospital and pattern of their antimicrobial susceptibility. Methodology: This descriptive study was carried out at Lahore General Hospital (LGH), Lahore, during January to December 2017. The lower respiratory samples i.e. sputum, broncho-alveolar lavage (BAL), tracheal secretions, endotracheal tips, tracheostomy tubes, chest drains and pleural fluid were obtained from 923 patients. The samples were collected aseptically and processed at Department of Pathology, PGMI, Lahore. The bacteria were identified according to microbiological tests and their antimicrobial susceptibility was done according to Clinical and Laboratory Standards Institute (CLSI). Results: Total 923 samples were received, 607 were positive on culture (65.7%). The most common isolated bacteria from all these specimens were Pseudomonas aeruginosa 217 (35.74%). Cefoperazone-sulbactam and piperacillin-tazobactam were the most sensitive antibiotics having >70% of sensitivity. Staphylococcus aureus were isolated in 55 (8.73%) of specimens, out of which 73% were reported as MRSA. Conclusion: The present study showed the microbiological pattern of bacteria in samples of LRTIs and trend of their antimicrobial susceptibility at LGH. The commonest bacterium was Pseudomonas aeruginosa. Cefoperazone-sulbactam and piperacillin-tazobactam were the most sensitive antibiotics